Tumor Targeting: A Highly Efficient Tumor‐Targeting Nanoprobe with a Novel Cell Membrane Permeability Mechanism (Adv. Mater. 12/2019). Issue 12 (19th March 2019) - Lei, Zhendong; Ding, Lin; Yao, Chenjie; Mo, Fengfeng; Li, Chenchen; Huang, Yanan; Yin, Xuelian; Li, Min; Liu, Jinliang; Zhang, Yong; Ling, Changquan; Wang, Yanli
Abstract : A graphene‐based tumor cell nuclear targeting fluorescent nanoprobe (GTTN) can recognize tumor cells at a very early stage by the cell membrane permeability targeting (CMPT) mechanism and track the invasion and metastasis of tumor cells at the single cell level through the differences of cell membrane permeability between normal cells and tumor cells. In article number1807456, Changquan Ling, Yanli Wang, and co‐workers observe an improvement in the tumor‐targeting rate from less than 5% to more than 50%.